+0  
 
0
27
1
avatar+761 

Help.

 
NotSoSmart  Oct 10, 2017
social bar
Sort: 

1+0 Answers

 #1
avatar+76837 
+2

-4.5x - 2y  = -12.5   (1)

3.25x - y  = -0.75    →   y =  3.25x + 0.75   (2)

 

Put (2)  into (1)

 

-4.5x - 2 (  3.25x + 0.75 )  = -12.5       simplify

 

-4.5x - 6.5x - 1.5  = -12.5

 

-11x  - 1.5  = -12.5      add 1.5 to both sides

 

-11x  = -11       divide both sides by   -11

 

x  = 1

 

And using ( 2)

 

y =  3.25 (1)  + 0.75   =   4

 

 

 

cool cool cool

 
CPhill  Oct 10, 2017

24 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details